Expression of human TLR4/myeloid differentiation factor 2 directs an early innate immune response associated with modest increases in bacterial burden during Coxiella burnetii infection. Issue 7 (October 2019) - Robison, Amanda; Snyder, Deann T; Christensen, Kelly; Kimmel, Emily; Hajjar, Adeline M; Jutila, Mark A; Hedges, Jodi F
Human TLR4 (hTLR4) and mouse TLR4 molecules respond differently to hypo-acylated LPS. The LPS of Coxiella burnetii is hypo-acylated and heavily glycosylated and causes a minimal response by human cells. Thus, we hypothesized that mice expressing hTLR4 molecules would be more susceptible to C. burnetii infection. Our results show that transgenic mice expressing hTLR4 and the human myeloid differentiation factor 2 (MD-2) adaptor protein (hTLR4/MD-2) respond similarly to wild type mice with respect to overall disease course. However, differences in bacterial burdens in tissues were noted, and lung pathology was increased in hTLR4/MD2 compared to wild type mice. Surprisingly, bone marrow chimera experiments indicated that hTLR4/MD-2 expression on non-hematopoietic cells, rather than the target cells for C. burnetii infection, accounted for increased bacterial burden. Early during infection, cytokines involved in myeloid cell recruitment were detected in the plasma of hTLR4/MD2 mice but not wild type mice. This restricted cytokine response was accompanied by neutrophil recruitment to the lung in hTLR4/MD2 mice. These data suggest that hTLR4/MD-2 alters early responses during C. burnetii infection. These early responses are precursors to later increased bacterial burdens and exacerbated pathology in the lung. Our data suggest an unexpected role for hTLR4/MD-2 in non-hematopoietic cells during C. burnetii infection.